A Single-Domain Antibody Targeting Complement Component C5 Acts as a Selective Inhibitor of the Terminal Pathway of the Complement System and Thus Functionally Mimicks the C-Terminal Domain of the Staphylococcus aureus SSL7 Protein - Yatime, Laure; Merle, Nicolas S.; Hansen, Annette G.; Friis, Niels Anton; Østergaard, Jakob A.; Bjerre, Mette; Roumenina, Lubka T.; Thiel, Steffen; Kristensen, Peter; Andersen, Gregers R. (Frontiers in Immunology, 2018)
The complement system is an efficient anti-microbial effector mechanism. On the other hand abnormal complement activation is involved in the pathogenesis of multiple inflammatory and hemolytic diseases. As general inhibition of the complement system may jeopardize patient health due to increased susceptibility to infections, the development of pathway-specific complement therapeutics has been a long-lasting goal over the last decades. In particular, pathogen mimicry has been considered as a promising approach for the design of selective anti-complement drugs. The C-terminal domain of staphylococcal superantigen-like protein 7 (SSL7), a protein secreted by Staphylococcus aureus, was recently found to be a specific inhibitor of the terminal pathway of the complement system, providing selective inhibition of cell lysis mediated by the membrane attack complex (MAC). We describe here the selection by phage display of a humanized single-domain antibody (sdAb) mimicking the C-terminal domain of SSL7. The antibody, called sdAb_E4, binds complement C5 with an affinity in the low micromolar range. Furthermore, sdAb_E4 induces selective inhibition of MAC-mediated lysis, allowing inhibition of red blood cell hemolysis and inhibition of complement deposition on apopto-necrotic cells, while maintaining efficient bactericidal activity of the complement terminal pathway. Finally, we present preliminary results indicating that sdAb_E4 may also be efficient in inhibiting hemolysis of erythrocytes from patients with paroxysmal nocturnal hemoglobinuria. Our data provide a proof of concept for the design of a selective MAC inhibitor capable of retaining complement bacteriolytic activity and this study opens up promising perspectives for the development of an sdAb_E4-derived therapeutics with application in the treatment of complement-mediated hemolytic disorders.